Purificação parcial, caracterização e estudos de ancoragem molecular da pirofosforilase do moniliophthora perniciosa - Santos Junior, Manoelito Coelho dos (2012)
The enzyme UDP-N-acetylglucosamine pyrophosphorylase Moniliophthora perniciosa, pathogenic fungus that causes witches' broom disease in Theobroma cacao, was the central focus of this work. The enzyme was purified and characterized, finally, using a 3D model of pyrophosphorylase’s docking study was performed. The witches' broom caused deep impact in the Bahia economy. Consequently, measures for its control were used, but without success. Thus, several researches involving more specific targets are being developed for the selection of more selective and economically viable antifungal agents. The enzyme has pyrophosphorylase structural and functional characteristics in different eukaryotic and prokaryotic organisms, so the development of inhibitors to it, should be based on organism which is being studied. The enzyme of the fungus M. perniciosa was partially purified by ammonium sulfate precipitation and gel filtration chromatography on Sephacryl S-200. The response surface methodology (RSM) was used to obtain the optimal pH and temperature. As a result, four different isoenzymes (PyroMp I, PyroMpII, PyroMpIII and PyroMpIV) showed that the optimum pH range of 6.9 to 8.4, and temperature ranging between 28-68 ° C. Based on the characteristics of substrates and products ten inhibitors were selected, which were refined by AM1. Docking studies between these compounds and enzyme were performed by AutoDock Vina software, following of refinement by molecular dynamics simulations. The results of docking suggest that the molecular recognition of the enzyme with the substrate occur mainly by hydrogen bonds between ligands and Arg116, Arg383, Gli381, and Lis408 aminoacids; and few hydrophobic interactions with Tir382 and Lys 123 residues. Among the compound analyzed, the NAG5 showed the best binding energy (-95.2 kcal/mol). The next steps for the control of witches' broom involve the attainment of the compound studied and the respective in vitro and in loco tests.